What do emergency physicians in charge do? A qualitative observational study. Issue 3 (10th March 2017) - Hosking, Ian; Boyle, Adrian; Ahmed, Vazeer; Clarkson, John
Abstract : Introduction: The emergency physician in charge role has developed in many large EDs to assist with patient flow. We aimed to describe and classify the problem-solving actions that this role requires. Methods: We interviewed senior emergency physicians and performed iterative, qualitative observations, using continuous reflective inquiry, in a single centre. We reviewed and classified these approaches by consensus. Results: Nine different problem-solving approaches were identified. These are deflecting, front loading, placing, plucking, flooding, targeting, chasing, guiding and juggling. These are useful for training and developing our understanding of how to manage an ED. Conclusions: Emergency physicians in charge have a number of problem-solving approaches that can be readily defined. We have described and categorised these. These results are potentially useful for developing decision support software.